2017
DOI: 10.15282/ijame.14.1.2017.4.0314
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of injected sprays of different bio-diesel fuels by using a common rail setup controlled by a programmable electronic system

Abstract: Biodiesel fuels are increasingly attracting interest in the scientific community and in the world motor industry. The morphological analysis of injected sprays is a key factor to increase engine performances using new biodiesel fuels and to compare them with those related to the use of conventional fuels. In this paper, an experimental setup is realised to carry out test campaigns, in order to analyse and compare the spray injections of different fuel typologies. A PC-interfaced electronic system was realised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Few studies were conducted to understand the injected spray behaviour through morphological analysis. The studies in this approach showed higher penetration values for biodiesel fuels due to their viscosity and drops in superficial tension, which facilitate a deeper penetration as compared to those obtained with conventional diesel fuels [20]. As biodiesel fuels need to be produced from bio-resources, it thus requires large amounts of bio-resources.…”
Section: Effective Abatement Of Diesel Engine Emissions With Split Inmentioning
confidence: 96%
“…Few studies were conducted to understand the injected spray behaviour through morphological analysis. The studies in this approach showed higher penetration values for biodiesel fuels due to their viscosity and drops in superficial tension, which facilitate a deeper penetration as compared to those obtained with conventional diesel fuels [20]. As biodiesel fuels need to be produced from bio-resources, it thus requires large amounts of bio-resources.…”
Section: Effective Abatement Of Diesel Engine Emissions With Split Inmentioning
confidence: 96%
“…The preheating of biodiesel at different temperatures reduces the viscosity and surface tension which enhances better fuel injection, improves mixture formation, and thereby better fuel atomisation. From the fuel properties, viscosity can affect fuel flow rate and cause poor fuel atomisation during the combustion process [9][10][11][12]. The use of biodiesel or its blend has effects on fuel droplet formation, vaporisation, and airfuel mixing process due to its higher viscosity [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Countries in other regions face severe crisis in bridging the gap between energy demand and fuel supply [2]. Fossil fuel combustion also results in air pollution, acid rain, and build-up of carbon dioxide, thus putting human beings and the environment at risk [3][4][5][6][7]. Among the alternatives to fossil fuels, biofuels such as biogas, alcohols, and biodiesels have received considerable attention due to their renewable nature and their inherent potential to bring down net CO2 emission [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%